Drip irrigation with treated wastewater from cashew nut industry under service pressures - Silva, Ketson Bruno da; Silva Júnior, Manuel Januário da; Batista, Rafael Oliveira; Santos, Delfran Batista dos; Batista, Raquel Oliveira; Lemos Filho, Luis César de Aquino (Semina: Ciências Agrárias, 2014)
The agricultural use of wastewater generated in the processing of cashew nuts enables the rationalization of water use, as well as the minimization of pollution and environmental degradation. The study aimed to analyze the effect of service pressures in the distribution uniformity of drip irrigation units applying treated wastewater from cashew nut industry. The experiment was conducted in split-split plots scheme having the service pressures (70, 140, 210 and 280 kPa) on parcels, the emitters models (G1, G2 and G3) on subplots and the evaluation periods (0, 20, 40, 60, 80, 100, 120, 140 and 160 h of operation of the irrigation units) on subsubplots. The treatments were distributed in a completely randomized design with three replications. The coefficient of uniformity of distribution of irrigation units, as well as the physical, chemical and microbiological characteristics of the effluent were determined every 20 hours of operation the irrigation units to totalize 160 h. The combination of dripper G3 and service pressure of 140 kPa provided excellent levels of distribution uniformity of effluent on irrigation units operating with treated wastewater of cashew nut industry. For application of treated wastewater from cashew nut it is not recommended the use of drippers with low flow rate (? 1.6 L h-1) and labyrinth of greater length (? 58 mm).